ANALISIS FINANSIAL DAN STRATEGI PENGEMBANGAN NANAS MADU DI KABUPATEN LAMPUNG TIMUR - Dita Pratiwi; Ali Ibrahim Hasyim; M Irfan Affandi (Lampung University, 2016)
This research purposes to: (1) analyze the farming financial feasibility of honey pineapple, and (2) know the priority strategies that must be done for the farming development of honey pineapple. This research was located in East Lampung District which was chosen purposively. Respondents taken were 67 farmers. The first purpose was analyzed quantitatively by financial analysis (Net B/C, NPV, IRR and Payback Periode) using compounding factor (CF) and discount factor (DF) 14%. The second purpose was analyzed descriptively by SWOT analysis. The result showed that the farming of honey pineapple in East Lampung is feasible and profitable. Financially the farming was feasible because the value of NPV and Net B/C were bigger than 1, and the value of IRR was bigger than interest rate. The priority strategies for Farming Development of honey pineapple were ; (1) utilizing fertile and vast field to increase the production for market domination (2) utilizing the easily available production facilities and suitable climate to increase the production, (3) producing good quality of goods to dominate the market.Key words : developments strategic, financial analysis,and honey pineapple